Literasi Media Digital untuk Guru Pembimbing dan Anak Pekerja Migran Indonesia di Sanggar Bimbingan (SB) At-Tanzil Malaysia - Anis Kurli; Rillia Aisyah Haris; Roos Yuliastina; Syamsul Arifin; Hidayat ,; Deny Fardiansyah Putra (Fakultas Sosial dan Ilmu Politik Universitas Wiraraja, 2025)
In its journey, digital media has given rise to important issues that need to be considered in its development. The knowledge skills in using and utilizing digital media (digital literacy) of PMI children at SB At-Tanzil Malaysia do not yet have sufficient knowledge to access digital media. The purpose of carrying out international community service activities at the At-Tanzil Malaysia Guidance Center is to increase the creativity of mentor teachers in providing teaching to PMI children at SB At-Tanzil and as a provision for Indonesian migrant workers' children in operating digital media in a healthy and appropriate manner, so that they do not make mistakes in accessing various kinds of information at the age of children. The methods used are Adult Training: this involves a more structured and formal approach, often with a focus on developing specific skills, Introduction to Digital Literacy: this includes teaching children about the positive and negative impacts of digital devices and appropriate digital usage behavior, Utilization of Learning Media: Using digital tools such as laptops or tablets as learning media, and Digital Literacy Training as a Moral Education Media. The benefits of this activity are changes in the behavior of teachers and PMI children in Malaysia who attend SB At-Tanzil towards a more creative and productive understanding of digital media. The results of this activity are being able to think critically, creatively and innovatively in learning activities, especially for supervising teachers to educate children with more enthusiasm and improve their psychomotor skills so that learning is better and easier to understand, and easy to solve problems that occur in learning.